(untitled) (Journal of International Studies, 2023)
The notion of historic rights forms the major basis to the claim by China to ‘islands’ in the South China Sea and the adjacent waters which are located within what is known as the nine-dash line. The South China Sea Arbitration case (Philippines v. China) has shown divergence between China’s interpretation of historic rights and the territorial acquisition regime under positive international law. This paper argues that Islamic international law has clearer principles on historic rights that do not upset the territorial sovereignty of coastal states. However, these principles must be appraised in the correct context of Islamic international law because it subscribes to a different approach to state sovereignty. Due to the importance of historic rights in this paper, the authors used both black letter and historical approaches to legal research. With historical legal research, the authors looked at the historical facts objectively in order to know how legal rules on sovereignty claims over maritime areas are formed throughout history particularly from the perspective of Islamic international law. This paper enables Islamic international law to offer a middle ground in which the proponents and opponents of China’s historical rights claims could meet.